MODERN METHODS OF LOCAL TREATMENT OF PATIENTS WITH UVEAL MELANOMA WITH LIVER METASTASES - L.O. PETROV; V.V. KUCHEROV; E.A. KRUGLOV; A.P. PETROSYAN; V.V. NAZAROVA; V.M. UNGURYAN (Avicenna Tajik State Medical University, 2022)
Uveal melanoma (UM) is a common malignant tumor of the eye, more aggressive than skin melanoma, resistant to anticancer drug treatment, having a poor prognosis and a high potential for metastasis, which is often limited to the liver and in up to 90% of cases unresectable. The median overall survival in these patients is 7 months. Progression-free survival is significantly higher in the topical versus systemic chemotherapy group. Local therapy includes transarterial chemoembolization, immunoembolization, radioembolization, and isolated liver chemoperfusion. The latter is a promising method and provides a high concentration of a chemotherapy treatment confined to the liver exceeding the allowable for systemic chemotherapy, thus preventing systemic toxicity. The provision of regional hyperthermia and hyperoxia potentiates the therapeutic effect. The use of this method for UM metastases limited to the liver showed the highest median overall survival of 17.1-24 months. Due to technical complexity and resource intensity, the global cumulative experience is about 300 procedures. Unsatisfactory results of systemic antitumor treatment for UM liver metastases prompt us to look for new ways of local treatment.